206k views
3 votes
In the Problem 2x-3=3x- 12 the 3x and the 2x are known as

User Altblue
by
5.0k points

1 Answer

3 votes

Answer:

Hence the value of 2x and 3x are 18 and 27 respectively.

Explanation:

Given the expression 2x - 3 = 3x - 12. We need to get the value of x first;

2x - 3x = -12 + 3

-x = -9

x = 9

Get 2x;

2x = 2(9)

2x = 18

Get 3x;

3x = 3(9)

3x = 27

Hence the value of 2x and 3x are 18 and 27 respectively.

User Matagus
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.